Conductive Polymers: Open‐Shell Donor–Acceptor Conjugated Polymers with High Electrical Conductivity (Adv. Funct. Mater. 24/2020). (11th June 2020) - Huang, Lifeng; Eedugurala, Naresh; Benasco, Anthony; Zhang, Song; Mayer, Kevin S.; Adams, Daniel J.; Fowler, Benjamin; Lockart, Molly M.; Saghayezhian, Mohammad; Tahir, Hamas; King, Eric R.; Morgan, Sarah; et al.
Abstract : In article number 1909805, Jason D. Azoulay and co‐workers demonstrate the design and development of open‐shell conjugated polymers that are electrically conductive in their native "undoped" form. A comparative study of structural variants, processing methodologies, and morphological features demonstrate that the conductivity could be tuned over many orders of magnitude to achieve a record high for an undoped material of 8.18 S cm −1 .